2015
DOI: 10.1111/1471-0528.13542
|View full text |Cite
|
Sign up to set email alerts
|

Association between in utero zidovudine exposure and nondefect adverse birth outcomes: analysis of prospectively collected data from the Antiretroviral Pregnancy Registry

Abstract: ObjectiveTo examine the association between nondefect adverse birth outcomes and in utero exposure to zidovudine (ZDV)‐containing regimens versus non‐ZDV antiretroviral (ARV) regimens.DesignAnalysis of prospectively‐collected data.SettingGlobal.Population HIV‐infected pregnant women prenatally exposed to antiretrovirals.MethodsEstimation of prevalence of and risk for nondefect adverse birth outcomes among HIV‐infected women.Main outcome measuresPrevalence of and risk for nondefect adverse birth outcomes.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…In a meta-analysis (35 studies: 20 prospective cohorts, 12 retrospective cohorts, three case-control studies), HIV infection in women not receiving ART was clearly associated with preterm birth, low birthweight, small for gestational age (SGA), and stillbirth, especially in sub-Saharan Africa (10). Recent data on prevalence of congenital abnormalities in HEU children, and associations with in utero ART exposure are presented in Table 1, which are consistent with the literature to date, indicating a similar risk of defects as in the general population (11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Adverse Pregnancy Outcomes Congenital Abnormalities Cardiasupporting
confidence: 83%
“…In a meta-analysis (35 studies: 20 prospective cohorts, 12 retrospective cohorts, three case-control studies), HIV infection in women not receiving ART was clearly associated with preterm birth, low birthweight, small for gestational age (SGA), and stillbirth, especially in sub-Saharan Africa (10). Recent data on prevalence of congenital abnormalities in HEU children, and associations with in utero ART exposure are presented in Table 1, which are consistent with the literature to date, indicating a similar risk of defects as in the general population (11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Adverse Pregnancy Outcomes Congenital Abnormalities Cardiasupporting
confidence: 83%
“…Low birth weight and preterm birth were more frequent in the combined ART group compared to AZT monotherapy [ 29 ]. Data from the American Antiretroviral Pregnancy Registry from 1989 to 2013 also found an increased risk for low birth weight among patients utilizing AZT regimens [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…A review of studies published between 1980 and 2017 compared women receiving tenofovir vs nontenofovir cART regimens during pregnancy and found no increased miscarriage risk, 47 and a study of zidovudine vs nonzidovudine cART regimens found a protective effect for miscarriage. 48 Meanwhile, PIs may lower progesterone levels, 49 possibly leading to adverse pregnancy outcomes including miscarriage, 50 preterm birth, 19 and lower birthweight. 20 History of miscarriage was not associated with miscarriage in our adjusted models.…”
Section: Figurementioning
confidence: 99%